Spondylocostal dysostosis 1 - case report and literature review - Elżbieta Drachal; Paweł Zapolnik; Łukasz Dembiński; Michał Zgurski; Antoni Pyrkosz (Termedia Publishing House, 2023)
Spondylocostal dysostosis (SCD) type 1 (also known as Jarcho-Levin syndrome) is a rare hereditary skeletal disorder. The mutation of the DLL3 gene leads to the Notch signalling pathway disorder, resulting in somitogenesis errors and numerous deformations within the spine and ribs. This article presents the diagnostic process of a 3-year-old girl suspected of SCD type 1. Performing Sanger method sequencing of the DLL3 gene and computed tomography imaging with 3D reconstruction allowed us to recognize the condition and confirm its molecular basis. We also performed array-based comparative genomic hybridization and detected an incidental finding - a terminal duplication in chromosome X. The whole clinical approach and special investigations may help clinicians recognise the disease and genetic counselling.